2019
DOI: 10.1590/s0102-865020190080000006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclosporine on ischemia-reperfusion injuries in rat kidneys. An experimental model

Abstract: PurposeTo assess Cyclosporine A (CsA) therapy at an intraperitoneal dose of 15 mg.kg -1 in a rodent model of non-septic renal ischemia.MethodsTwenty male Wistar rats were randomized to receive CsA therapy or none therapy before undergoing 30 minutes of renal ischemia followed by reperfusion. Additionally, 10 rats were randomized to undergo the same surgical procedure of the aforementioned animals with neither ischemia nor CsA therapy. Twelve hours after kidney ischemia, the left kidneys were evaluated for hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…[5,17] Serum levels of biomolecules such as BUN, urea, creatinine and Cys C are elevated in ARF. [14,[18][19][20] In this study, the findings that the mean BUN and urea levels in the RIRI group were significantly higher than those in the sham control group indicated that the experimental model was established correctly. The similarity of the mean BUN and urea levels in the RIRI + oxerutin and sham control groups supported to the protective effect of oxerutin in RIRI.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[5,17] Serum levels of biomolecules such as BUN, urea, creatinine and Cys C are elevated in ARF. [14,[18][19][20] In this study, the findings that the mean BUN and urea levels in the RIRI group were significantly higher than those in the sham control group indicated that the experimental model was established correctly. The similarity of the mean BUN and urea levels in the RIRI + oxerutin and sham control groups supported to the protective effect of oxerutin in RIRI.…”
Section: Discussionmentioning
confidence: 96%
“…[12] Many studies have shown that the duration of ischemia for the development of RIRI is 30 min. [13][14][15] However, reperfusion times ranging from 1 h to 24 h were evaluated in the studies. [13][14][15][16] Since we considered that the improvement of early-stage RIRI will be a positive recovery sign for the late-stage renal functions, we conducted our RIRI model in such a way that 30 min of ischemia followed by 1 h of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of this study, they stated that dexmedetomidine may have a protective effect on renal IR damage, but there is no such evidence for remifentanil [ 17 ]. In a recently published study, it has been reported that cyclosporine A given 15 mg/kg intraperitoneally does not prevent the harmful effects of IR damage in rat kidneys [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is an active metabolite of fungi in soil and has strong immunosuppressive effects. [20][21][22] CsA can reversibly and selectively alter the function of T-lymphocytes, prevent the transcription of lymphokine genes, interfere with signaling, 19 inhibit release of IL-2, interferon and other immune factors, alter humoral and cellular immunity, inhibit the killing activity of natural killer cells, and inhibit the differentiation and proliferation of lymphocytes. 23,24 ETO is used for general anesthesia and is a safe imidazole derivative.…”
Section: Discussionmentioning
confidence: 99%